Transcranial versus Endoscopic Transsphenoidal Approaches in Management of Recurrent Giant Pituitary Adenomas - Ismail, Mohamed; Abdel Aleem Abdel Moneim Ragab, Omar; Salama, Mohamed M.; Ayoub, Basim M.; Elmahdy, Wael (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this study was to compare the transcranial and the endoscopic transsphenoidal approaches for patients with recurrent giant pituitary adenomas as regards the extent of tumor resection and the clinical outcome. METHODS: The study included 21 patients with recurrent giant pituitary adenomas divided into two groups; Group A included nine patients operated on by transcranial approaches and Group B included 12 patients operated on by the endoscopic transsphenoidal approach. Both groups were compared as regards the extent of tumor resection and the post-operative clinical outcome, particularly the visual and endocrinological outcomes, in addition to morbidity and mortality. RESULTS: There was a higher incidence of total and near-total resection in Group B (41.7%) and a higher incidence of subtotal resection in Group A (55.6%). The incidence of visual improvement was higher in Group B (55.6%) than in Group A (28.6%). Post-operative biochemical remission was achieved in 100% of Group B patients and in 50% of Group A patients with functioning adenomas. The incidence of post-operative complications was higher in Group A (77.8%) than in Group B (50%). CONCLUSION: The endoscopic transsphenoidal approach for recurrent giant pituitary adenomas is associated with a higher extent of tumor resection, better rates of visual improvement and endocrinological remission, and lower incidence of complications. The transcranial approach should be reserved for some adenomas with marked lateral or anterior extensions, fibrous tumors, and after the failure of the endoscopic transsphenoidal approach.